Evaluation of Glacial Lake Outburst Flood Susceptibility Using Multi-Criteria Assessment Framework in Mahalangur Himalaya - Khadka, Nitesh; Chen, Xiaoqing; Nie, Yong; Thakuri, Sudeep; Zheng, Guoxiong; Zhang, Guoqing (Frontiers in Earth Science, 2021)
Ongoing recession of glaciers in the Himalaya in response to global climate change has far-reaching impacts on the formation and expansion of glacial lakes. The subsequent glacial lake outburst floods (GLOFs) are a significant threat to lives and livelihoods as they can cause catastrophic damage up to hundreds of kilometres downstream. Previous studies have reported the rapid expansion of glacial lakes and several notable destructive past GLOF events in the Mahalangur Himalaya, suggesting a necessity of timely and updated GLOF susceptibility assessment. Here, an updated inventory of glacial lakes across the Mahalangur Himalaya is developed based on 10-m Sentinel-2 satellite data from 2018. Additionally, the GLOF susceptibilities of glacial lakes (≥0.05 km2) are evaluated using a multi-criteria-based assessment framework where six key factors are selected and analyzed. Weight for each factor was assigned from the analytical hierarchy process. Glacial lakes are classified into very low, low, medium, high, and very high GLOF susceptibility classes depending upon their susceptibility index based on analysis of three historical GLOF events in the study area. The result shows the existence of 345 glacial lakes (>0.001 km2) with a total area of 18.80 ± 1.35 km2 across the region in 2018. Furthermore, out of the 64 glacial lakes (>0.05 km2) assessed, 7 were identified with very high GLOF susceptibility. We underline that pronounced glacier-lake interaction will likely increase the GLOF susceptibility. Regular monitoring and more detailed fieldworks for these highly susceptible glacial lakes are necessary. This will benefit in early warning and disaster risk reduction of downstream communities.